PERBANDINGAN DUA PRODUK DIGITAL CONTROL SYSTEM - Dicky Suryapranatha (Industry Xplore, 2021)
Digital Control System (DCS) is a very important tool for manufacturing companies that implement automation systems in their production processes, so companies must be careful when deciding to purchase DCS tools offered by vendors. This study aims to compare two Digital Control System (DCS) devices from international suppliers using temperature comparison variables, data processing speed and data transfer speed. After the data collected is tested for validity and reliability, then a T test is carried out to compare these variables and a direct comparison of the material specifications of the two tools is carried out. The results of the Benchmarking study are that there is a difference in the temperature and data processing speed variables between the two DCS devices, while for the data transfer rate variable there is no difference. This difference occurs because the data computing process is more and more data computing is needed, the temperature will increase and for data processing speed there is no difference because it uses the same technology. To improve the capabilities of the DCS tool, it is necessary to redesign for the controller, design panels and use the latest data transfer technology and data security systems in data transfer.